Development of a Community-Oriented Parasitological Survey as a Teaching Strategy for Medical Students - Tatiana Ascencio (American Society for Microbiology, 2012)
Parasitic diseases remain a serious public health problem in developing countries, especially in such tropical countries with weak environmental sanitation as El Salvador (located in Central America), and cause health problems like anemia, cognitive disorders, and malnutrition. Antiparasitic drugs are available for treatment, but community education is also necessary to prevent these diseases. By introducing a community-oriented parasitological survey into our Medical Parasitology and Mycology course (MPM), we hypothesized that exposing students to a real-life situation would help them acquire knowledge and skills required in their professional practice. This survey is also suitable for use by clinical laboratory students, nursing students (for educational purposes on the prevention of parasitic diseases), and general biology students (because they need to know the suitable process of obtaining a stool sample and the proper diagnosis of the parasites).